Analysis of Mathematical Models for Design and correlation time series Studies, Projects and Research Papers - Milla Lostaunau, Luis (2000)
studies, and research projects require mathematical models that optimize the trajectory of the curve obtained from a historical sample or a set of data obtained in the field or in the laboratory so that its variables are appropriate to the same.